2020
DOI: 10.3390/app10165521
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Evaluation of Thermal Performance of Solar Heating System Using Al2O3 Nanofluid

Abstract: Over the years, solar collecting systems have gained interest in renewable energy. This study investigated improving the efficiency of the working fluid in thermal solar systems by using nanofluids with three concentrations of alumina, 0.1, 0.3, and 0.5 wt%. The UV-vis absorbance, electronic conductivity, and thermal transfer properties of the nanofluids were analyzed, and the thermal changes with exposure to solar radiation in an experimental collector system were measured by pyranometer. The electronic condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…They concluded that the temperature increases for the 0.1 wt.%, 0.3 wt.%, and 0.5 wt.% alumina nanofluids were 3.1%, 12.5%, and 13.9% higher, respectively, than distilled water (DW). Shin et al [25] reported that, in the same experiments of [24], the temperature increases for the 0.01 wt.%, 0.05 wt.%, and 0.1 wt.% CNTs/water nanofluids were 13.6%, 18.2%, and 22.1% higher than that of DW, respectively. Both studies suggested that the efficiency could be further improved by using different types of nanoparticles and dispersion methods in addition to alumina and CNTs nanofluids.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…They concluded that the temperature increases for the 0.1 wt.%, 0.3 wt.%, and 0.5 wt.% alumina nanofluids were 3.1%, 12.5%, and 13.9% higher, respectively, than distilled water (DW). Shin et al [25] reported that, in the same experiments of [24], the temperature increases for the 0.01 wt.%, 0.05 wt.%, and 0.1 wt.% CNTs/water nanofluids were 13.6%, 18.2%, and 22.1% higher than that of DW, respectively. Both studies suggested that the efficiency could be further improved by using different types of nanoparticles and dispersion methods in addition to alumina and CNTs nanofluids.…”
Section: Introductionmentioning
confidence: 88%
“…The concentrations of nanoparticles dispersed in the DW (0 wt.%) were 0.01 wt.%, 0.1 wt.%, and 1 wt.% for 300 mL of nanofluid. The total volume of the working fluid was 1000 mL in previous studies [24,25]. The total volume of the working fluid was reduced to 300 mL to obtain rapid results in this experiment, which can shorten the experimental time required to obtain the results.…”
Section: Preparation Of Nanofluidsmentioning
confidence: 95%
See 1 more Smart Citation
“…Its use in the field of renewable and sustainable energy technologies allows for creating high-efficient and more economic systems. In this regard, many research studies [1][2][3][4][5][6][7][8] have evaluated, theoretically and experimentally, the increase in performance in heat transfer applications and solar thermal systems associated with the use of alumina-water as working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Solar thermal systems are non-polluting and do not emit greenhouse gases during their operation. They could also save considerable fossil fuel and electricity consumption, which is currently used for domestic applications [1,2] since conventional heat transfer fluids have many limitations, such as poor thermal conductivity, high viscosity, uncontrollable pressure drop, and pumping power. Researchers have found a new class of heat transfer fluid (HTF) called 'nanofluids', which is defined as a colloidal suspension of nanosized solid particles incorporated with common base fluids to obtain superior thermophysical properties such as thermal conductivity, viscosity, density, and specific heat capacity.…”
Section: Introductionmentioning
confidence: 99%